Fluid management strategy in dengue acute respiratory distress syndrome with chronic kidney disease: A case report - Devarakonda Prithvi; Ajeet Kumar; Amarjeet Kumar (Wolters Kluwer -Medknow Publications, 2024)
Pulmonary manifestation in dengue is due to the involvement of both the upper and lower airways. Severe forms of dengue infection (pleural effusion, dengue hemorrhagic shock syndrome, and acute respiratory distress syndrome [ARDS]) are mainly due to the involvement of the lower respiratory tract. ARDS is a well-known respiratory complication following dengue infection. Patients with chronic kidney disease (CKD) diagnosed with dengue had a higher risk of unfavorable outcomes. Pulmonary involvement is one of the life-threatening complications in patients having CKD that contributes to increasing the mortality rate. Dysregulation of cytokines and apoptotic signaling pathway is a nonclassical mechanism of the kidney-lung crosstalk that results in the development of acute kidney injury in patients having ARDS. Severe worsening of renal function is common in CKD patients with dengue. Here, we discuss fluid management strategy in a patient having CKD who developed ARDS following dengue infection. The difficulty in the therapeutic dilemma is attributable to ambiguity in liberal versus conservative fluid therapy, contributing to a high risk of mortality. The narrow window of fluid tolerance in CKD patients further complicates the resuscitation strategy in patients with dengue ARDS.